2016
DOI: 10.1007/s10853-016-0569-1
|View full text |Cite
|
Sign up to set email alerts
|

Linking microstructural evolution and macro-scale friction behavior in metals

Abstract: A correlation is established between the macro-scale friction regimes of metals and a transition between two dominant atomistic mechanisms of deformation. Metals tend to exhibit bi-stable friction behavior --low and converging or high and diverging. These general trends in behavior are shown to be largely explained using a simplified model based on grain size evolution, as a function of contact stress and temperature, and are demonstrated for pure copper and gold. Specifically, the low friction regime is linke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 63 publications
12
92
0
Order By: Relevance
“…The average grain size in this layer was measured to be 9 nm, which is also similar to the 10 nm grain size found in the original sample. These findings help support the model proposed by Argibay et al [38] since it seems that the surface layer converges to nearly the same average grain size for an identical level of applied surface stress. Moreover, the grain size distribution also spanned the range of 3 -40 nm, indicating that both fine-grained (d < 10 nm) and coarser-grained (d > 10 nm) films of Ni-19 at.% W evolve to an identical structure.…”
Section: Subsurface Evolution In Annealed D = 45 Nm Samplesupporting
confidence: 90%
See 2 more Smart Citations
“…The average grain size in this layer was measured to be 9 nm, which is also similar to the 10 nm grain size found in the original sample. These findings help support the model proposed by Argibay et al [38] since it seems that the surface layer converges to nearly the same average grain size for an identical level of applied surface stress. Moreover, the grain size distribution also spanned the range of 3 -40 nm, indicating that both fine-grained (d < 10 nm) and coarser-grained (d > 10 nm) films of Ni-19 at.% W evolve to an identical structure.…”
Section: Subsurface Evolution In Annealed D = 45 Nm Samplesupporting
confidence: 90%
“…For the d = 45 nm sample, grain-boundary-mediated plasticity should be shut off and Figure 8 even shows evidence of mottled contrast inside many grains, providing evidence of dislocation plasticity. A major proposition in this area is that the steady-state grain size changes as a function of applied surface stress [38,39]. Additional experimental evidence of this claim would help to validate and inform this model.…”
Section: Subsurface Evolution In Annealed D = 45 Nm Samplementioning
confidence: 99%
See 1 more Smart Citation
“…[25,26] In this context and for linking the mechanical properties, and consequently the microstructure, of a metal with its tribological properties Argibay and co-workers recently brought forward a feedback cycle. [27] The authors assume that different surface stresses will lead to a variation in how the material responds to shearing, i.e., by grain boundary sliding or by dislocation motion which therefore depend on the normal load during a tribological experiment. To visualize this concept, a feedback loop between grain size, friction coefficient and surface stress was developed which highlights the need to know the stress field under the sliding bodies.…”
Section: Introductionmentioning
confidence: 99%
“…In a tribological system, where two bodies are moving relative to each other with a certain speed under the application of a normal force (F N ) and along a certain distance with certain environmental conditions (e.g., temperature and humidity), there are other aspects, such as the surface finish [1][2][3][4] and the microstructure [5][6][7], that affect the wear, the friction and even the tribo-oxidation on the contact zone. Furthermore, it has been shown that intermittent tribological loading induces plastic deformation in a layer beneath the wear track in the tribologically transformed zone (TTZ) [8], which could result in grain refinement (in initially coarse-grained materials) [4,9] or grain coarsening (in initially nanocrystalline materials) [4,6,7,10,11].…”
Section: Introductionmentioning
confidence: 99%